Prospecção do molusco invasor Limnoperna fortunei (Dunker, 1857) nos principais corpos hídricos do estado do Paraná, Brasil - Pestana, Debora; Ostrensky, Antonio; Tschá, Marcel Kruchelski; Boeger, Walter A. (Papéis Avulsos de Zoologia, 2010)
Were collected in the main water bodies of the state of Paraná (Brazil) it will seek the golden mussel larvae, Limnoperna fortunei (Dunker, 1857). This species of mussel is colonizing various water bodies in South America since its introduction in Argentina in 1991. Already reached the Paraná and Paraguay rivers, having reported their presence in the states of Mato Grosso do Sul, Paraná, Sao Paulo, Minas Gerais and Rio Grande do Sul. Samples were collected in winter and spring of 2007 and summer and autumn 2008 in 14 sampling points along the rivers Iguaçu, Piquiri, Ivaí (tributaries of the Paraná River) and Tibagi (tributary of the Paranapanema river). This study determined the presence of this species throughout all parts of the Iguaçu River, in two sites of Piquiri and a sample point of the Tibagi river. In the Ivaí River, their presence was not detected at any point in any season. Based on the results, was made a map of occurrence of the species in the state of Paraná. These results are useful to base a decision concerning the advancement of the species in order to monitor their presence and/or prevent their entry into other water bodies in the state.